Comfort and Satisfaction Patients in the Interaction Process Viewed from the Caring Behavior of Nurses: Literature Review - Trianti, Indri Retno; Lestari, Ayu Budi; Ula, Lutfi Arifatul (Open Access Health Scientific Journal, 2024)
Background: The patient's sense of comfort is related to the patient's satisfaction with receiving nursing services. The low quality of nursing services is in line with low satisfaction, so it is necessary to improve the quality of nursing services to increase satisfaction. One of the comfort and satisfaction factors is the ability to provide information, caring, communicating, polite, responsive. Caring nurses are a caring attitude that makes it easier for patients to achieve improved health and recovery. Caring behavior is a form of caring, giving attention to others, being person-centred, respecting self-esteem and humanity, commitment to preventing worsening health status, paying attention and respecting others.Methods: The design used is a literature review, namely using several journals from several sources such as Google Scholar and Pubmed which were published from 2010-2020.Results: That there is a relationship between patient comfort and satisfaction in the interaction process in terms of nurses' caring behavior. And it can be seen that the lower patient comfort will be in line with the lower patient satisfaction.Conclusion: Caring nurses are a caring attitude that makes it easier for patients to achieve improved health and recovery. Caring behavior is a form of caring, giving attention to others, being person-centred, respecting self-esteem and humanity, commitment to preventing worsening health status, paying attention and respecting others.